Causal relationship between 412 gut microbiota, 1,400 blood metabolites, and diabetic nephropathy: a randomized Mendelian study - Cao, Bo-Ning; Zhang, Cai-Yan; Wang, Zhen; Wang, Yao-Xian (Frontiers in Endocrinology, 2025)
ObjectiveThe aim of this study was to investigate the causal relationship between microbiota, diabetic nephropathy, and blood metabolites through a randomized Mendelian study.MethodsIn this study, we used 412 microbiota as exposures, 1,400 blood metabolites as intermediaries, and diabetic nephropathy as the outcome. We conducted a two-way Mendelian randomization (MR) analysis to explore the causal relationship between microbiota and diabetic nephropathy, followed by mediation analyses and two-step MR to identify potential blood metabolites.ResultsThere is a causal relationship between microbiota and diabetic nephropathy. Specific bacteria and metabolites, such as Escherichia coli str. K-12 substr. MG1655, Listeria monocytogenes 10403S, g_Adlercreutzia, g_Haemophilus, g_Bacteroides, and Escherichia coli CFT073, and metabolites like pyrraline, glycocholenate sulfate, alpha-ketoglutarate, tetradecadienoate (14:2), Cys-gly oxidized, methylsuccinate, and various others, were identified. Escherichia coli str. K-12 substr. MG1655 is positively related to alpha-ketoglutarate levels, while alpha-ketoglutarate levels and Sphingomyelin (d18:1/18:1, d18:2/18:0) are negatively related. The bacterial microbiota involved in fatty acid oxidation is associated with diabetic kidney disease (DKD) progression, positively correlated with glycocholenate sulfate levels, and negatively correlated with the phosphate linoleyl-tetraenyl-glycerol (18:2 to 20:4) ratio. Additionally, Listeria monocytogenes 10403S is positively correlated with N-acetyl-isoputreanine and negatively correlated with X-12462. Anaerobic fermentation-related bacteria were positively related to N-acetylcarnitine and 5-acetylamino-6-formyluracil and negatively correlated with 5-acetamino-6-amino-3-methyluracil (X-24243). Escherichia coli CFT073 was positively associated with X-16580. Interactions between Bacillus species and metabolites such as d18:1/18:1, d18:2/18:0, 2-aminophenol sulfate, and cholate were negative when compared to tetradecadienoate (14:2). g_Adlercreutzia is positively correlated with N-delta-acetylornithine, methylsuccinate, and N-acetyl-isoputreanine but negatively correlated with N-acetylglucosamine and N-acetylgalactosamine. g_Haemophilus was positively associated with arachidoylcarnitine but negatively correlated with X-24531. The results were heterogeneous and multi-efficacious.ConclusionsFor the first time, MR analysis provides supportive evidence for a bidirectional causal relationship between microbiota and diabetic nephropathy and identifies specific genes associated with the disease. The results suggest that probiotic therapy may play a significant role in preventing diabetic nephropathy and improving the quality of life and survival rates of affected patients. Furthermore, this study provides additional evidence of a causal relationship between specific microbiota, diabetic nephropathy, and blood metabolites.